The Anti-inflammatory Effects of Hydrogen-Rich Water Acts in a Volume-Dependent Manner on Rats' Lungs Exposed to Cigarette Smoke - A Sitti Rahmatullah; Arif Santoso; Muhammad Husni Cangara; Ika Yustisia; Aminuddin Aminuddin; Endy Adnan (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2023)
Cigarette smoke can activate various ROS-sensitive signaling pathways in the lungs, triggering airway inflammation and leading to mucus hypersecretion. Meanwhile, hydrogen has shown anti-inflammatory activity in various injury models. This study aims to determine the anti-inflammatory effect of hydrogen-rich water on lungs exposed to cigarette smoke in rats. Male wistar rats were divided into four groups randomly (n=5), namely CI group (given aquades + exposed to free air), CII group (given aquades + exposed to cigarette smoke), HI group (given HRW 5 mL once a day + exposed to cigarette smoke), and HII group (given HRW 5 mL twice a day + exposed to cigarette smoke). HRW/aquades was administered orally 30 minutes before cigarette smoke exposure. Exposure to cigarette smoke lasts about 15-25 minutes with 5 cigarettes/day for 28 days. Subsequently, we examine the levels of lung NF-kB p65 using the ELISA method and perform pulmonary histopathological examination. The results showed that the administration of HRW reduced the levels of NF-κB p65 induced by cigarette smoke exposure, which is significant in the HII group (p<0.01). From the histopathological examination, administration of HRW significantly reduced the degree of lung inflammation caused by cigarette smoke exposure in the HI and HII group (p<0.05).